Death and dying as a literary device: a reading of selected works by contemporary Malaysian writers - Ali Termizi, Arbaayah; Mohd Noor, Nurul Soleha; Wan Salim, Wan Iman (International Journal of Languages, Literature and Linguistics, 2017)
There is no reliable information of death as an experience and it remains until now as an unknown but trustworthy mystery. Hence death has to be encountered in ways known to readers via the help of fiction. In literature death, both physical and physiological exists at many levels. Though the idea of death is infinite, it never fails to provide meaning to the development of a narrative because it contributes to the emotional effects, plots twists, suspense and mysteries. In addition it adds closure to the plot, a closure which is not alien to most detective / crime fiction and horror / ghost stories. Presumably death has to be meaningful in these genres in order to be treated as an important part of human existence and thus elevated its status as a significant literary device. What about other genres? Is it justifiable to use death as the ultimate fear in order to tighten the plot or add weightage to the drama in genres other than the ones mentioned earlier? Thus this paper aims to analyse how death is employed as a literary device by contemporary Malaysian writers and to study whether the fear of death (or the dead) as expounded by Freud is necessary in these works. It shall focus on the ways of dying, the disclosure of death news and other character/s reaction towards the news in selected works in order to answer the research questions. Preliminary findings from this paper are expected to establish the utilization of death as a literary device in works by contemporary Malaysian writers.